Identifying Ecological Distribution Conflicts Around the Inter-regional Flow of Energy in Turkey: A Mapping Exercise - Aydin, Cem Iskender (Frontiers in Energy Research, 2019)
The consumption of more energy in Turkey is seen as a precondition for the economic and social development of the country in line with its comprehensive ideology of modernization and progress, and hence, a rather aggressive strategy in energy infrastructure investments is adopted since mid-2000s. Because of this aggressive strategy involving expropriation and enclosure of commons societal unrest against the electricity plants at local scale escalated even further, creating numerous local environmental justice conflicts all over the country. While electricity generation in Turkey is mostly carried out at the rural setting, electricity is consumed mostly in the urban setting, where both the household and industrial consumption levels are higher. A comparison of the regional distribution of electricity generation and consumption in Turkey shows that while the electricity generation capacity is concentrated in some cities—Izmir, Sakarya, Adana, Hatay, Zonguldak, Çanakkale, Muğla, and Samsun to name a few—it is mostly consumed in the urbanised centres of the country, more particularly in Istanbul, Kocaeli, Bursa, Ankara, and Izmir (the industrialised cities, considered as the engine of growth in the country). Hence, it would not be wrong to say that some cities such as Çanakkale and Zonguldak are designated as “ecological sacrifice zones” for the sake of national growth, illustrating well how Turkey prioritises economic growth (and thus industrialisation) over just ecological distribution. At this background, this paper focuses on the ecological distribution conflicts over electricity generation infrastructures and attempts to provide a mapping of the different electricity generation projects (in operation, under construction or planned) to better understand the urban-rural interplay over the electricity consumption and production. Hence, it attempts to shed light on the growing number of environmental conflicts for the last three decades, following the aggressive neo-liberal policies of modernisation and industrialisation.